Perception towards the performance of outboard motors among Malaysian coastal fishermen in Manjung, Perak - Ismail Zainol,; Omar Yaakob,; Mohd Rajali Jalal, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Fishermen, particularly those in coastal seas, are often categorized under low-income community. Many efforts have been taken to assist this community to sustain their livelihoods, but hampered by various factors such as high operational cost. Coastal fishing boats specifically made from fiberglass are greatly dependent on petrol-powered outboard motor to generate power. The high fuel consumption of outboard motors is believed one of the factors that contribute to their high operational cost. To this end, it is necessary to dive into the fishermen’s perception on this issue. This paper presents finding on the perception of coastal fishermen towards the performance of outboard motors and their views on fuel-saving engines. Some key areas are discussed and explained in this paper. A questionnaire had been developed as a survey tool; divided into three parts, covering cost factor, engine factor and operation factor. The questionnaire was developed based on Likert scale and distributed to randomly selected respondents among the fishermen community at Manjung, Perak. The data was then processed using Statistical Package for Social Science (SPSS). The results showed that inshore fishermen are not satisfied with petrol outboard motor, with more than 95% confidence level.